2021
DOI: 10.3389/fphar.2021.646628
|View full text |Cite
|
Sign up to set email alerts
|

Galangin Inhibits Gastric Cancer Growth Through Enhancing STAT3 Mediated ROS Production

Abstract: Galangin, a flavonoid isolated from the rhizome of Alpinia officinarum (Hance), exerts anticancer activities against many cancer cells such as liver cancer, breast cancer, lung cancer and esophageal cancer. However, the effect, as well as the underlying molecular mechanism of galangin on gastric cancer remains to be elucidated. In the present study, galangin inhibited cell viability of MGC 803 cells but not normal gastric mucosal epithelial GES-1 cells. It suppressed cell proliferation accompanied by reduced K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 33 publications
(18 reference statements)
0
17
0
Order By: Relevance
“…On the other hand, one of the biggest challenges in cancer treatment is the ongoing autocrine and paracrine activation of proinflammatory transcription factors, such as NF- κB, signal transducer and activator of transcription 3 (STAT-3), activator protein 1 (AP-1), forkhead box protein M1 (FOXM1), and hypoxia-inducible factor 1α (HIF-1α) that drive the overproduction of diverse mediators of inflammation—inflammatory cytokines, chemokines, cellular adhesion molecules, anti-apoptotic molecules, and iNOS [ 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 ]. Regarding propolis and its components, numerous studies have demonstrated the anti-inflammatory effects of various flavonoids [ 1 , 2 , 3 , 4 , 38 , 174 , 198 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 ]. The anti-inflammatory properties of several flavonols (quercetin, rutin, and morin) and flavanones (hesperetin and hesperidin) were examined in animal models of acute and chronic inflammation.…”
Section: Molecular and Cellular Targets Of Propolis And Its Flavonoid...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, one of the biggest challenges in cancer treatment is the ongoing autocrine and paracrine activation of proinflammatory transcription factors, such as NF- κB, signal transducer and activator of transcription 3 (STAT-3), activator protein 1 (AP-1), forkhead box protein M1 (FOXM1), and hypoxia-inducible factor 1α (HIF-1α) that drive the overproduction of diverse mediators of inflammation—inflammatory cytokines, chemokines, cellular adhesion molecules, anti-apoptotic molecules, and iNOS [ 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 ]. Regarding propolis and its components, numerous studies have demonstrated the anti-inflammatory effects of various flavonoids [ 1 , 2 , 3 , 4 , 38 , 174 , 198 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 ]. The anti-inflammatory properties of several flavonols (quercetin, rutin, and morin) and flavanones (hesperetin and hesperidin) were examined in animal models of acute and chronic inflammation.…”
Section: Molecular and Cellular Targets Of Propolis And Its Flavonoid...mentioning
confidence: 99%
“…The observed anti-inflammatory effects of propolis are attributed to the presence of flavonoids, especially galangin. Galangin inhibits COX and LOX activity, and reduces PGE2 release and the expression of the inducible isoform of COX (COX-2) [ 161 , 249 , 250 ]. Besides galangin, many authors [ 240 , 251 , 252 , 253 , 254 ] have emphasized the anti-inflammatory contribution of quercetin.…”
Section: Molecular and Cellular Targets Of Propolis And Its Flavonoid...mentioning
confidence: 99%
“…In a recent study, galangin and chrysin were determined to be the most abundant polyphenols of a brown propolis extract [ 3 ]. Galangin, 3,5,7-trihydroxyflavone, is recognized to have significant beneficial biological activities such as anticancer [ 4 , 5 ], antioxidant [ 6 , 7 ]. Galangin is also found in plants such as Alpinia officinarum Hance (Zingiberaceae), or lesser galangal, and has been used as a spice and in herbal remedies for a variety of ailments in Ayurvedic and Chinese medicine for centuries [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The activities of NOX family members (including NOX1-5, DUOX1, and DUOX2) are tightly related to the generation of ROS ( 48 ). STAT3 is also reported to bind to the NOX1 promoter and increase the production of NOX1 which subsequently stimulates the production of O2 •− ( 49 ). Therefore, the regulation of overactivated STAT3 in microglia is essential to regulate microglial activation, ROS level and neuroinflammation, all of which are tightly related to neuron damage in stroke.…”
Section: Discussionmentioning
confidence: 99%